Preliminary evidence for an association between intake of high‐fat high‐sugar diet, variations in peripheral dopamine precursor availability and dopamine‐dependent cognition in humans. (3rd December 2020) - Hartmann, Hendrik; Pauli, Larissa K.; Janssen, Lieneke K.; Huhn, Sebastian; Ceglarek, Uta; Horstmann, Annette
Abstract: Obesity is associated with alterations in dopaminergic transmission and cognitive function. Rodent studies suggest that diets rich in saturated fat and refined sugars (HFS), as opposed to diets diets low in saturated fat and refined sugars (LFS), change the dopamine system independent of excessive body weight. However, the impact of HFS on the human brain has not been investigated. Here, we compared the effect of dietary dopamine depletion on dopamine‐dependent cognitive task performance between two groups differing in habitual intake of dietary fat and sugar. Specifically, we used a double‐blind within‐subject cross‐over design to compare the effect of acute phenylalanine/tyrosine depletion on a reinforcement learning and a working memory task, in two groups that are on opposite ends of the spectrum of self‐reported HFS intake (low vs high intake: LFS vs HFS group). We tested 31 healthy young women matched for body mass index (mostly normal weight to overweight) and IQ. Depletion of peripheral precursors of dopamine reduced the working memory specific performance on the operation span task in the LFS, but not in the HFS group ( P  = 0.016). Learning from positive‐ and negative‐reinforcement (probabilistic selection task) was increased in both diet groups after dopamine depletion ( P  = 0.049). As a secondary exploratory research question, we measured peripheral dopamine precursor availability (pDAP) at baseline as an estimate for central dopamine levels. The HFS group had a significantly higher pDAP at baseline compared to the LFS group ( P  = 0.025). Our data provide the first evidence indicating that the intake of HFS is associated with changes in dopamine precursor availability, which is suggestive of changes in central dopamine levels in humans. The observed associations are present in a sample of normal to overweight participants (ie, in the absence of obesity), suggesting that the consumption of a HFS might already be associated with altered behaviours. Alternatively, the effects of HFS diet and obesity might be independent. Abstract : Rodent studies suggest that consumption of a high‐fat high‐sugar diet impacts on the brain's dopaminergic system. Should the same hold for humans, a diet high in saturated fat and added sugar should impact on dopamine‐mediated cognition. Here we show that acute peripheral dopamine precursor depletion impacts differently on working memory performance in groups that differ in their self‐reported consumption of saturated fat and added sugar. Moreover, we provide preliminary evidence indicating that a diet high in saturated fat and added sugar is associated with differences in peripheral availability in dopamine precursors in humans.